Therapeutic Potential of Mesenchymal Stem Cells and Their Products in Lung Diseases—Intravenous Administration versus Inhalation - Fröhlich, Eleonore (Pharmaceutics, 2021)
The number of publications studying the therapeutic use of stem cells has steadily increased since 2000. Compared to other applications, there has been little interest in the evaluation of mesenchymal stem cells (MSCs) and MSC-derived products (mostly extracellular vesicles) for the treatment of respiratory diseases. Due to the lack of efficient treatments for acute respiratory distress syndrome caused by infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the action of MSCs has also been studied. This review describes mode of action and use of MSCs and MSC-derived products in the treatment of lung diseases including the respective advantages and limitations of the products. Further, issues related to standardized production are addressed. Administration by inhalation of MSCs, compared to intravenous injection, could decrease cell damage by shear stress, eliminate the barrier to reach target cells in the alveoli, prevent thrombus formation in the pulmonary vasculature and retention in filter for extracorporeal membrane oxygenation. There is more feasible to deliver extracellular vesicles than MSCs with inhalers, offering the advantage of non-invasive and repeated administration by the patient. Major obstacles for comparison of results are heterogeneity of the products, differences in the treatment protocols and small study cohorts.